Heart rate variability after vigorous physical exercise is positively related to loss aversion - Molins, F.; Serrano, M. A. (Anxiety, Stress and Coping, 2021)
Background and Objectives: Loss aversion bias, whereby losses loom larger than gains, can be reduced by stress. At the same time, vigorous physical exercise is a powerful neuroendocrine stressor and heart rate variability (HRV) provides an objective measure of the actual exercise impact, relative to each individual physical condition. Our aim was to study whether vigorous exercise can influence loss aversion, considering HRV in this relation. We hypothesized that the lower HRV derived from vigorous exercise (i.e., when stressor produced the most impact) would predict a lower loss aversion. Methods: Two groups (Experimental, N = 37; Control, N = 39) completed a loss aversion task, but the experimental group was exposed to an acute physical stressor before. Results: Results revealed a significant group x HRV interaction. In the control group, HRV was not associated with loss aversion. Conversely, as hypothesized, the lower HRV levels derived from exercise were associated with a lesser loss aversion in the experimental group. Conclusions: Results suggest that physiological changes from physical exercise could affect decision-making by reducing loss aversion.